ANALISIS PENELITIAN HADIS MELALUI METODE PARSIAL DAN SIMULTAN DALAM DHAIF ADABUL MUFRAD TENTANG NAFKAH SEORANG SUAMI PADA KELUARGANYA BAB 96 HADITS NOMER 115 - Mohammad Ruslan (Akademika, 2018)
Abstract: This paper aims to discuss about hadis classified as dhoif by  Al-Bani in his book Dhaif Adabul Mufrad al- Imam Bukhari based on hadis analysis about basic necessities of husband to his family, as stated in hadis 96  no 115. This hadis is classified as hadis mauquf because ar-Rajul referred to Shahaby or Rasulullah friends, when the writer traced the hadis based on simultaneous analysis, this hadis classified as hadis dho’if  by al-Bani is absolutely correct. The hadis text  is not considered shad or contradicted to the history of the Quran. So It is shohihul matan. But the writer found any other aspect of rawi like Ismail bin Rofi' and clasified as Majhul like Al-Walid.Keywords: Simultaneous analysis, dhaif adabul mufrad, basic necessities of husband